Canalostomy is an ideal surgery route for inner ear gene delivery in big animal model. (2nd November 2019) - Ji, Xiao-Jun; Chen, Wei; Wang, Xiao; Zhang, Yue; Liu, Qian; Guo, Wei-Wei; Zhao, Jian-Guo; Yang, Shi-Ming
Abstract: Background: Inner gene therapy offers great promises as a potential treatment for hearing loss. Aims/objectives: One of the critical determinants of the success of inner ear gene therapy is to find a delivery method which results in consistent transduction efficiency of targeted cell types while minimizing hearing loss. Material and methods: Surgery was performed only in the right ear of each Bama miniature pig, and the left ear served as a control. The gene delivery to inner ear via round window membrane (RWM) and posterior semicircular canal (PSC) approach was performed with the viral vector AAV1-CMV-GFP. Results: The gene delivery through RWM and the PSC (canalostomy) is able to perfuse the inner ear. Conclusions and significance: The easy anatomic identification of the PSC, as to RWM, as well as minimal manipulation of the temporal bone required, make this surgical approach an attractive option for inner ear gene delivery in big animal model.